2018
DOI: 10.3390/cancers10080260
|View full text |Cite
|
Sign up to set email alerts
|

LY2157299 Monohydrate, a TGF-βR1 Inhibitor, Suppresses Tumor Growth and Ascites Development in Ovarian Cancer

Abstract: Transforming growth factor beta (TGF-β) signaling has pleiotropic functions regulating cancer initiation, development, and metastasis, and also plays important roles in the interaction between stromal and cancer cells, making the pathway a potential therapeutic target. LY2157299 monohydrate (LY), an inhibitor of TGF-β receptor I (TGFBRI), was examined for its ability to inhibit ovarian cancer (OC) growth both in high-grade serous ovarian cancer (HGSOC) cell lines and xenograft models. Immunohistochemistry, qRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 54 publications
(85 reference statements)
6
46
0
Order By: Relevance
“…3) implicating activation of TGF-β signaling in OC metastasis. Supporting the proposed importance of TGF-β in metastases, we have demonstrated that inhibition of TGF-β signaling delays tumor growth and suppresses ascites development in OC xenograft models [18]. Collectively these observations demonstrate the potential of TGF-β signaling targeting as a therapeutic strategy in HGSOC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…3) implicating activation of TGF-β signaling in OC metastasis. Supporting the proposed importance of TGF-β in metastases, we have demonstrated that inhibition of TGF-β signaling delays tumor growth and suppresses ascites development in OC xenograft models [18]. Collectively these observations demonstrate the potential of TGF-β signaling targeting as a therapeutic strategy in HGSOC.…”
Section: Discussionsupporting
confidence: 58%
“…The stimulatory contribution of stroma in tumor progression, coupled with the fact that stroma is more genetically stable compared with cancer cells, has led to stroma increasingly being recognized as a therapeutic target [16,17]. In support of this, we recently published that inhibition of TGF-β signaling, which suppresses the cancer-stroma interplay, can delay tumor growth and ascites development in MES subtype HGSOC patient-derived xenografts [18]. In comparison with the advances in our understanding of cancer cell biology, our knowledge of the nature and roles of stromal contribution has lagged.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to this study showing benefit of TGFBR2 blockade, another recent study using the TGFBR1 small molecule inhibitor LY2157299/ Galunisertib showed promise in several EOC xenograft models. 34 They showed that LY215729 treatments prior to EOC cell injection, and throughout tumor outgrowth, led to reduced ascites development and tumor growth. 34 Given these recent findings, it will be important to test whether pretreatment of mice with our inhibitory TGFBR2 antibodies leads to improved efficacy as a monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…34 They showed that LY215729 treatments prior to EOC cell injection, and throughout tumor outgrowth, led to reduced ascites development and tumor growth. 34 Given these recent findings, it will be important to test whether pretreatment of mice with our inhibitory TGFBR2 antibodies leads to improved efficacy as a monotherapy. It will also be important to extend further testing of LY215729 to immune competent models of EOC in combination with chemotherapy and immunotherapy regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Interfering collagen biosynthesis enzymes Collagen genes MiR-129-5p, MiR-29b, MiR-384 [275][276][277] Prolyl 4-hydroxylase Budesonide, catechol, N-oxalylglycine, coumalic acid, ethyl dihydroxybenzoic acid [278][279][280] Heat shock protein 90 1G6-D7, dipalmitoyl-radicicol, 17-DMAG, ganetespib [281][282][283][284] Heat shock protein 47 MiR-29, 1,3-dimethylol-5-FU, AK778, pirfenidone, terutroban [285,286] Matrix metalloproteinases Gallium complex GS2, isoflavonoids, bisphosphonates [287,288] Lysyl oxidases Beta-aminopropionitrile [289] Disturbing cancer cell signaling pathways Snail transcription factors Toosendanin, ponicidin, ferulic acid [290] Hypoxia-inducible factor Tamoxifen, 28-O-propynoylbetulin [291,292] STAT3 signaling pathway VS-4718, stattic, ruxolitinib, S3I-201 [293,294] TGF-β signaling pathway LY2157299 monohydrate, trabedersen, fresolimumab, galunisertib [295,296] NF-κB signaling pathway Honokiol, aspirin, ormeloxifene [297][298][299] AKT signaling pathway Quetiapine, pirfenidone [300] Notch signaling pathway Rovalpituzumab tesirine, taladegib, crenigacestat, MiR-148a [301] Hedgehog signaling pathway Itraconazole, sonidegib, vismodegib [302] RAS signaling pathway Perindopril, losartan [100,303] Tyrosine kinase receptor Bevacizumab, imatinib, ponatinib, dasatinib [304,305] Discoidin domain receptor WRG-28, 7rh, AZD0156 [306][307][308] G protein family receptor AT13148, KD025, Azaindole 1, chelerythrine…”
Section: Effects Of Inhibitors Targeted Sites Of Inhibitors Typical Imentioning
confidence: 99%